Satisfaction Levels of Medical Attendants at a Pakistani Emergency Department - Ashraf, Jibran (Cureus, 2020)
Introduction Healthcare services all over Pakistan are facing an ever-growing patient flow. Rapid urbanization and a population boom are mainly responsible for this phenomenon. This is most evident in the emergency department. Not only are the patients in dire need of medical management but they require it within a certain time frame lest it is too late. It is difficult in such situations to deliver satisfactory services. Many studies have analyzed satisfaction levels in doctors, nurses, postgraduates, and patients in the emergency department. But little data is available on the satisfaction levels of attendants that accompany the patients most of the time. Attendants are an integral part of the doctor-patient relationship and their perspective may offer some insight into the shortcomings and issues afflicting the system, especially with regards to emergency medicine. Aim To evaluate the satisfaction levels of attendants of patients treated at the emergency department. Materials and methods This is a cross-sectional study, held from January 1 to June 31, 2018. Patient and attendant confidentiality were ensured. Written consent was taken in all cases. Attendants of patients treated at the emergency department that followed up at four weeks were given a simple questionnaire to fill. There were 10 questions in it, with a simple “Yes” or “No” answer. A “Yes” answer carried one point while a “No” answer had zero points. Satisfaction levels were scored out of 10. Satisfaction levels were grouped as very satisfied (9-10 points), satisfied (7-8 points), partially satisfied/partially dissatisfied (5-6 points), dissatisfied (3-4 points), and very dissatisfied (0-2 points). Results A total of 688 patients followed up at four weeks, with their attendants willing to fill in the questionnaire. Mean satisfaction levels were 7.21 ± 4.59. Almost 60% of the attendants were either very satisfied or satisfied with their experience. Attendants were most satisfied with the cost, lab facilities, availability of medicines, and medical equipment. Time management was the most concerning factor for the attendants. Conclusions Attendants are mostly very satisfied or satisfied with their experience in the emergency department. About one-fifth are either very dissatisfied or dissatisfied.